Digital creatives and the rethinking of religious authority - Campbell, Heidi, 1970- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
"Much speculation was raised in the 1990s, during the first decade of internet research, about the extent to which online platforms and digital culture might challenge traditional understandings of authority, especially in religious contexts. Digital Creatives and the Rethinking of Religious Authority explores the ways in which religiously-inspired digital media experts and influencers online challenge established religious leaders and those who seek to maintain institutional structures in a world where online and offline religious spaces are increasingly intertwined. In the twenty-first century, the question of how digital culture may be reshaping notions of whom or what constitutes authority is incredibly important. Questions asked include: Who truly holds religious power and influence in an age of digital media? Is it recognized religious leaders and institutions? Or religious digital innovators? Or digital media users? What sources, processes and/or structures can and should be considered authoritative online, and offline? Who or what is really in control of religious technological innovation? This book reflects on how digital media simultaneously challenges and empowers new and traditional forms of religious authority. It is a gripping read for those with an interest in communication, culture studies, media studies, religion/religious studies, sociology of religion, computer-mediated communication, and internet/digital culture studies."--
Investigating approaches to the study of authority -- Defining religious digital creatives -- Christian digital creatives' performance of authority: Enacting media-making narratives and a technological apologetic -- Digital entrepreneurs: Internet-empowering visionary technology influencers -- Digital spokespersons: The rise of institutional identity curators -- Digital strategists: Acting as missional media negotiators -- How Christian digital creatives understand and perform authority -- How Christian digital creatives enact a technological apologetic -- Conclusion: Rethinking authority through the work of religious digital creatives.
OCLC-licensed vendor bibliographic record.
Keywords: Mass media in religion; Digital media -- Religious aspects -- Christianity; Social media -- Religious aspects -- Christianity; Authority -- Religious aspects -- Christianity; Christianity and culture; RELIGION / General